Rice Pi5-mediated resistance to Magnaporthe oryzae requires the presence of two coiled-coil-nucleotide-binding-leucine-rich repeat genes - Lee, Sang-Kyu; Song, Min-Young; Seo, Young-Su; Kim, Hye-Kyung; Ko, Seho; Cao, Pei-Jian; Suh, Jung-Pil; Yi, Gihwan; Roh, Jae-Hwan; Lee, Sichul; An, Gynheung; Hahn, Tae-Ryong; et al. (Oxford University Press, 2009)
Rice blast, caused by the fungus Magnaporthe oryzae, is one of the most devastating diseases of rice. To understand the molecular basis of Pi5-mediated resistance to M. oryzae, we cloned the resistance (R) gene at this locus using a map-based cloning strategy. Genetic and phenotypic analyses of 2014 F2 progeny from a mapping population derived from a cross between IR50, a susceptible rice cultivar, and the RIL260 line carrying Pi5 enabled us to narrow down the Pi5 locus to a 130-kb interval. Sequence analysis of this genomic region identified two candidate genes, Pi5-1 and Pi5-2, which encode proteins carrying three motifs characteristic of R genes: an N-terminal coiled-coil (CC) motif, a nucleotide-binding (NB) domain, and a leucine-rich repeat (LRR) motif. In genetic transformation experiments of a susceptible rice cultivar, neither the Pi5-1 nor the Pi5-2 gene was found to confer resistance to M. oryzae. In contrast, transgenic rice plants expressing both of these genes, generated by crossing transgenic lines carrying each gene individually, conferred Pi5-mediated resistance to M. oryzae. Gene expression analysis revealed that Pi5-1 transcripts accumulate after pathogen challenge, whereas the Pi5-2 gene is constitutively expressed. These results indicate that the presence of these two genes is required for rice Pi5-mediated resistance to M. oryzae.